Perbedaan Pengetahuan Dan Sikap Tentang Perilaku Jajan Sebelum dan Sesudah Edukasi Kesehatan Melalui Permainan Kartu Kuartet di SMPN 17 Kota Tasikmalaya Tahun 2023 - Salsabila, Milania; Fitriani, Sinta (Journal of Midwifery and Public Health, 2023)
Hawker food plays an important role in influencing the quality of human resources, especially in school children. This study aims to evaluate the differences in knowledge and attitudes of grade 7 students of SMPN 17 Kota Tasikmalaya about snacking behavior before and after receiving health education using quartet card game media. The research method used is Quasi Experimental with One Group Pretest-Posttest approach. The population consists of all grade 7 students of SMPN Kota Tasikmalaya, with a sample of 65 students who meet the inclusion criteria. The instruments used are questionnaires and quartet card game media. Data analysis using the Wilcoxon test and T test showed significant differences before and after health education, with P values for knowledge and attitudes being 0.000 < 0.05 respectively. Students need to increase their knowledge about the dangers of indiscriminate snacking through information retrieval, and schools can utilize the quartet card game media in health education activities for school children. This study showed an improvement in students' knowledge and attitudes after the educational treatment.